3D CP-XFEM modelling of short crack propagation interacting with twist/tilt nickel grain boundaries. (November 2022) - Zhang, Xiaoxian; Dunne, Fionn P.E.
Abstract: Short fatigue crack growth across grain boundaries of differing tilt and twist combinations has been investigated in three dimensions using coupled crystal plasticity and extended finite element methods. Crack path selection and growth rate are mechanistically determined by considering crystallographic planes containing the highest shear strain and the achievement of a critical stored energy density respectively. Tilt angle is found to have weak influence on crack growth rates approaching the grain boundary but increasing twist angle was shown to lead to higher growth rate retardation, as observed in experiments. Large twist angle was also shown to lead to multi-slip system activation as the crack tip traversed the grain boundary, potentially giving rise to multiple crack planes and hence faceted cracks. Elastic stored energy density was shown to capture observed sensitivity of crack growth rates and retardations to grain boundary tilt and twist, and in combination, thereby offering an improved metric over residual Burgers vector and geometric compatibility.